The sustainability revolution : portrait of a paradigm shift - Edwards, Andrés R., 1959- (New Society Publishers, 2005)
Sustainability has become a buzzword in the last decade, but its full meaning is complex, emerging from a range of different sectors. In practice, it has become the springboard for millions of individuals throughout the world who are forging the fastest and most profound social transformation of our time - the Sustainability Revolution. The Sustainability Revolution paints a picture of this largely unrecognized phenomenon from the point of view of five major sectors of society:Community (government and international institutions)Commerce (business)Natural Resources (forestry, farming, fisheries.